(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Automobile industry annually is to reduce harmful emissions into the environment. Anti-friction oil additives in automotive internal combustion engines is one way fight against friction losses which result from fuel economy, which in turn reduces the amount of harmful emissions vehicle exhaust. Assessment of the effectiveness of oil additives need to tribologycal properties for further analysis. For the purpose of this research is carried out in a variety of major friction equipment design studies, evaluating their properties and create an experimental facility with the assistance possible to evaluate changes in oil additives on friction over the existing components and their mutual friction.